ASPEK REPRODUKSI IKAN SELAR KUNING (Selaroides leptolepis) YANG DIDARATKAN DI PELABUHAN PERIKANAN NUSANTARA SUNGAILIAT - Fitra Dwi Anjani; Wahyu Adi; Eva Utami (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2018)
Yellowstripe scad fish (Selaroides leptolepis) which is in the port of Fisheries Port of Sungiliat has an important economic value. An assessment of the reproductive aspects of fish will provide basic information for appropriate utilization management efforts. This study aims to determine the reproductive aspect of Yellowstripe scad fish (Selaroides leptolepis) from March to May: Sex Ratio, Gonad Maturity Level (TKG), Gonad Maturity Index (IKG), and Fecundity. The study was conducted from March to May 2018. The sampling method was using random sampling. The results showed that the sex ratio of male and female fish was 1: 1.32. Male and female fish are in TKG II, III and TKG IV. The development of female fish gonads faster than males in terms of 3 months of study. Gonad Maturity Index of male fish ranged from 0.00419 to 0.008012 and female fish ranged from 0.00257 to 0.008083. Fecundity of fish ranged from 3630 - 16555 grains